Risk Factors of Cardiovascular Disease among a Hanoi-based University’s Staff - Thom, Vu Thi; Nga, Vu Van; Quynh, Do Thi; Mai Anh, Vu Thi (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 34 No 2DO - 10.25073/2588-1132/vnumps.4126, 2018)
Abstract: In recent years, Vietnam has witnessed an increase in cardiovascular disease morbidity and mortality.  This has given impetus to the current cross-sectional study to collect data on risk factors of cardiovascular disease through the 2016 annual physical exam result of 269 staff members aged from 20 to 64 from a Hanoi-based university. The prevalence of overweight - obesity, hypertension and dyslipidemia was 43.8%, 12.3% and 29.0%, respectively. Men were more at risk than women. Compared with wider community, the prevalence of hypertension and dyslipidemia among the staff was considerably lower. There was an association between gender and these risk factors, while age generally affected hypertension (p < 0.001). Keywords: Cardiovascular disease risk factors, overweight and obesity, hypertension, dyslipidemia. References: [1] WHO. Cardiovascular diseases (CVDs) Fact sheet 2017 [Available from: http://www.who.int/mediacentre/factsheets/fs317/en/. [2] Global Health Estimates 2015: Estimated deaths by age, sex and cause [Internet]. WHO. 2015. [3] Federation WH. Risk factors 2017 [23/7/2017]. Available from: https://www.world-heart-federation.org/resources/risk-factors/. [4] Bộ Y Tế. Chiến lược Quốc gia phòng chống bệnh không lây nhiễm giai đoạn 2015-2025. Hà Nội: Bộ Y tế; 2015. [5] Việt NL. Kết quả mới nhất điều tra tăng huyết áp toàn quốc năm 2015 – 2016. 2016. [6] Hạnh NTL. Tình trạng rối loạn dinh dưỡng Lipid và một số yếu tố liên quan ở người 25-74 tuổi nội thành Hà nội năm 2008. 2008. [7] Thắng TX. Nghiên cứu các yếu tố nguy cơ bệnh tim mạch ở người >25 tuổi tại 2 quận huyện Hà Nội. Viện Tim mạch trung ương: Đại học Y Hà Nội; 2013. [8] Lâm NT. Thống nhất phương pháp kỹ thuật sử dụng trong đánh giá thừa cân - béo phì của các nhóm tuổi khác nhau. Tạp chí DD&TP. 2003;1. [9] Bethesda. National High Blood Pressure Education Program. The Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure. 2004. [10] National Heart Lung and Blood Institute. National Cholesterol Education Program: ATP III Guidelines At-A-Glance Quick Desk Reference 2002. [11] Medicine Moh-GDoP. STEPS Vietnam 2015. 2016. [12] Tan Van Bui, Christopher Leigh Blizzard, Khue Ngoc Luong, Ngoc Le Van Truong, Bao Quoc Tran, Petr Otahal, et al. National survey of risk factors fornon-communicable disease in Vietnam: prevalence estimates and an assessment of their validity. BMC Public Health. 2016;16(498). [13] Quang Ngoc Nguyen, Son Thai Pham, Loi Doan Do, Viet Lan Nguyen, Stig Wall, Lars Weinehall, et al. Cardiovascular Disease Risk Factor Patterns and Their Implications for Intervention Strategies in Vietnam. International Journal of Hypertension. 2012;2012. [14] Oanh TH Trinh, Nguyen D Nguyen, Philayrath Phongsavan, Michael J Dibley, Bauman AE. Prevalence and risk factors with overweight and obesity among Vietnamese adults: Caucasian and Asian cut-offs. Asia Pac J Clin Nutr 2009;18(2):226-33. [15] Helen L Walls, Anna Peeters, Pham Thai Son, Quang NN. Prevalence of underweight, overweight and obesity in urban Hanoi, Vietnam. Asia Pac J Clin Nutr. 2009;18(2):234-9. [16] National Heart LaBI. Overweight and Obesity [Available from: https://www.nhlbi.nih.gov/health-topics/overweight-and-obesity. [17] Kiet A Ly, Thanh GN Ton, Quang V Ngo, Tung T Vo, Fitzpatrick AL. Double burden: a cross-sectional survey assessing factors associated with underweight and overweight status in Danang, Vietnam. BMC Public Health. 2013;13(35). [18] N. Jitnarin, V. Kosulwat, N. Rojroongwasinkul, A. Boonpraderm, Haddock CK. Prevalence of overweight and obesity in Thai population: Results of the National Thai Food Consumption Survey. Eat Weight Disord. 2011;16(4):242-9. [19] Hee-Taik Kang, Jae-Yong Shim, Hye-Ree Lee, Park B-J. Trends in Prevalence of Overweight and Obesity in Korean Adults, 1998–2009: The Korean National Health and Nutrition Examination Survey. Journal of Epiemiology. 2014;24(2):109-16. [20] WHO. Global Atlas on cardiovascular disease prevention and control. 2011. [21] Duc Anh Ha, Robert J. Goldberg, Jeroan J. Allison, Thang Hong Chu, Nguyen HL. Prevalence , Awareness , Treatment , and Control of HighBlood Pressur e: A Population -Based Survey in Thai Nguyen , Vietnam. PloS ONE. 2013;8(6). [22] Son PT. Hypertension in Vietnam, from comunity - based studies to a national targeted programme Umeå, Sweden: Umeå University, Hanoi Medical University; 2012. [23] H Van Minh, P Byass, NTK Chuc, Wall S. Gender differences in prevalence and socioeconomic determinants of hypertension: findings from the WHO STEPs survey in a rural community of Vietnam. Journal of Human Hypertension. 2006;20:109-15. [24] Kaplan NM. Cardiovascular risks of hypertension: UpToDate; 2016 [Available from: http://www.uptodate.com/contents/cardiovascular-risks-of-hypertension. [25] Association AH. Understand Blood Pressure readings 2016 [updated 15/09/2017. Available from: http://www.heart.org/HEARTORG/Conditions/HighBloodPressure/KnowYourNumbers/Understanding-Blood-Pressure-Readings_UCM_301764_Article.jsp#.WdCnNNoX7X4. [26] Bùi Thị Nhung, Bình TQ. Rối loạn lipid máu ở người không béo bụng và có chỉ số khối cơ thể bình thường. Tạp chí Y học dự phòng. 2016;10(183):190. [27] Wichai Aekplakorn, Surasak Taneepanichskul, Pattapong Kessomboon, Virasakdi Chongsuvivatwong, Panwadee Putwatana, Piyamitr Sritara, et al. Prevalence of Dyslipidemia and Management in the Thai Population, National Health Examination Survey IV, 2009. Journal of Lipids. 2014;2014:1-13. [28] Huỳnh Ngọc Linh, Nguyễn Thành Trung, Khóa TQ. Đặc điểm rối loạn lipid máu và các yếu tố liên quan ở người từ 35 tuổi trở lên tại tỉnh cà Mau năm 2015. Tạp chí Y học dự phòng.2016;4(177): 39. [29] Lê Thanh Chiến và các cộng sự. (2011), "Khảo sát mối tương quan giữa tăng huyết áp với BMI, vòng eo, tỉ số eo mông ở người dân phường Hòa Thạnh, quận Tân Phú ", Tạp chí Y học Thành phố Hồ Chí Minh. 15(4). [30] Trần Thị Mỹ Loan và Trương Quang Bình (2009), "Tương quan giữa chỉ số khối cơ thể và rối loạn lipid máu ở bệnh nhân tăng huyết áp", Tạp chí Y học Thành phố Hồ Chí Minh. 13(1). [31] Berit Lilienthal Heitmann (1992), "The effects of gender and age on association between blood lipid levels and obesity in Danish men and women aged 35-65 years", J Clin Epidemiol (45), tr. 693 - 702 [32] Kaare H. Bonaa và Dag S. Thelle (1991), "Association Between Blood Pressure and Serum Lipids in a Population", Circulation(83), tr. 1305-1314. [33] Ichiro Wakabayashi (2004), "Relationships of body mass index with blood pressure and serum cholesterol concentrations at different ages", Aging Clinical and Experimental Research(14), tr. 461-46